Differentially expressed genes (DEGs) analysis indicating 6-shogaol anticancer activity against HCT-116 Cells Performed Primarily by Affecting Genes in Common (shared-DEGs) of apoptotic and p53 signaling pathways - Tedjo, Aryo; Noor, Dimas R; Kusmardi,; Ramadanti, Nur Ayu; Amelia Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ginger have strong anti-inflammatory and antioxidant properties that can inhibit growth and trigger apoptosis of colorectal cancer cells. Dried ginger containing the main bioactive compound 6-shogaol is widely used for practical reasons in storage. In this study, the mechanism of 6-shogaol apoptosis was tried to be explained by looking at the Differentially Expressed Genes (DEGs) changes in HCT-116 cells. The results of DEGs analysis on Gene Expression Omnibus (GEO) data which contained gene expression data for the HCT-116 cell group treated with 6-shogaol and the control group showed that there were 142 DEGs of the apoptotic pathway with 9 (nine) of them being share-DEGs of the apoptotic pathway with other pathways related to apoptosis such as MAPK signaling pathway, p53 signalling pathway, and protein processing in endoplasmic reticulum pathways. Based on the regulation of the 9 share-DEGs, it was also explained that the apoptotic activity of 6-shogaol mainly occurs through the p53 signalling pathway which involves up-regulation of BAX, BBC3, GADD45G, and TNFRSF10A.